Advanced control of NO emission from algal biomass combustion using loaded iron-based additives. (15th October 2019) - Sun, Jin; Zhao, Bingtao; Su, Yaxin
Abstract: It has become an important energy and environmental issue how to effectively reduce NOx emissions from algae biomass combustion. To achieve advanced control of NO emission from algae biomass combustion, three kinds of iron-based additives, including Fe, Fe 2+ and Fe 3+, were physicochemical-loaded onto different algal biomasses using the immersion method which is different from the conventional physical blending. The effects of iron-based additives on NO emission were examined for various combustion temperatures, additive agents, and additive concentrations. Results showed that the higher the temperature, the greater the NO emissions from algal biomass combustion. However, the iron-based additives were able to inhibit NO emission in this process. The percentage drops in NO emission levels observed were 5.79–51.22%, 12.50–63.41%, and 14.06–80.49% for Fe, Fe 2+ and Fe 3+ based on a 1% loading rate. The inhibitory effects of Fe 2+ and Fe 3+ were comparable but better than those of Fe. Increasing the concentration of the iron-based additive load had a significant inhibitory effect. These results may provide a positive reference for combustion-, co-firing- and reburning-based NOx control for energy utilization of algae biomass. Graphical abstract: Image 10516 Highlights: Advanced control of NO emission from algal biomass combustion. Utilization of physicochemical-loaded iron-based additives for NO emission reduction. Fe 3+ and Fe 2+ had higher inhibitory effect on NO emissions than Fe 0 . Effects of concentration of additives were addressed. The possible N conversion mechanisms were discussed.